Stratified or Comprehensive? The Economic Efficiency of School Design - Giorgio Brunello; Massimo Giannini (Center for Economic Studies and ifo Institute (CESifo), 2001)
We study the efficiency of secondary school design by focusing on the degree of differentiation between vocational and general education. Using a simple model of endogenous job composition, we analyze the interaction between relative demand and relative supply of skills and characterize efficient school design when the government runs schools and cares about total net output. We show that neither a comprehensive nor a stratified system unambiguously dominates the other system in terms of efficiency for all possibile values of the underlying parameters. Since comprehensive systems generate more equal labor market outcomes, it follows that the relationship between efficiency and equity in secondary education is not necessarily a trade off. We also show that net output maximizing government policy is not always supported by majority voting. When schools are stratified, majority voting could increase the elitist nature of general schools by rising the admission standard above efficient levels. At the same time, and depending on the values of the underlying parameters, efficient stratified schools could be voted down in favor of less efficient comprehensive schools.
Keywords: 330